2020
DOI: 10.1155/2020/8814557
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among Nurses Working in Ethiopia

Abstract: Background. Burnout is a condition of emotional exhaustion, depersonalization, and low personal accomplishment that can occur among individuals who work with people in some capacity. Nursing is a stressful profession that deals with human aspects of health and illness and can ultimately lead to job dissatisfaction and burnout. Although burnout among nurses has been addressed in previous research, the heterogeneous nature of the result findings highlights the need for a detailed meta-analysis in Ethiopia. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…The study reported higher level of emotional exhaustion (mean=31.244) with most nurses (n=209, 90.1%) a rming it as indicated in Table 1. Similar studies undertaken at the Sub-Saharan African regions posit that high rates of burnout in a form of emotional exhaustion among nurses and midwives; and are usually attributed to work environments, work con icts, and lack of social support (31,47) Other researchers found emotional exhaustion among nurses working health care facilities in South Africa (49), Ethiopia (50) and Nigeria (51). It is well established that job stresses results from unsupportive practice environment, and it may affect the nurses' satisfaction, turnover intentions and the quality of care delivery to patients (52).…”
Section: Discussionmentioning
confidence: 82%
“…The study reported higher level of emotional exhaustion (mean=31.244) with most nurses (n=209, 90.1%) a rming it as indicated in Table 1. Similar studies undertaken at the Sub-Saharan African regions posit that high rates of burnout in a form of emotional exhaustion among nurses and midwives; and are usually attributed to work environments, work con icts, and lack of social support (31,47) Other researchers found emotional exhaustion among nurses working health care facilities in South Africa (49), Ethiopia (50) and Nigeria (51). It is well established that job stresses results from unsupportive practice environment, and it may affect the nurses' satisfaction, turnover intentions and the quality of care delivery to patients (52).…”
Section: Discussionmentioning
confidence: 82%
“…The study reported higher level of emotional exhaustion (mean = 31.244) with most nurses (n = 209, 90.1%) affirming it as indicated in Table 1. Similar studies undertaken at the Sub-Saharan African regions posit that high rates of burnout in a form of emotional exhaustion among nurses and midwives; and are usually attributed to work environments, work conflicts, and lack of social support [31,47] Other researchers found emotional exhaustion among nurses working in health care facilities in South Africa [48], Ethiopia [49] and Nigeria [50]. It is well established that job stresses results from unsupportive practice environment, and it may affect the nurses' satisfaction, turnover intentions and the quality of care delivery to patients [51].…”
Section: Discussionmentioning
confidence: 82%
“…Healthcare professionals often experience burnout (Chemali et al, 2019;Dubale et al, 2019). The results of the study revealed that nurses around the world have high burnout prevalence rates (Hailay et al, 2020;Shah et al, 2021;Woo et al, 2020). Worldwide studies on nurse burnout syndrome are often found in emergency or critical care settings have proved that burnout is a common problem in many countries (Adriaenssens et al, 2015; Alharbi et al, 2016;Hamed et al, 2020;Nobre et al, 2019).…”
Section: Introductionmentioning
confidence: 95%